Legal Framework for Sustainable Conservation of Fishery Resources in the Marine Environment of Nigeria - Moses-Oke, Roseline; Erhun, Mercy (Faculty of Law, Universitas Brawijaya, 2022)
It is impossible to overstate the value of effective fisheries sector management in a society like Nigeria. This will guarantee enough food at affordable prices and a source of social and economic advancement for the populace. Living ocean resources are in danger of becoming extinct due to the high harvesting rates. Over time, the legal measures enacted to safeguard the maritime environment and actions taken by the institutions tasked with upholding them have been shown to be insufficient and ineffectual. In this study, the management of fisheries and marine life resources and the difficulties it faces was evaluated using both primary and secondary sources of information. This was geared toward creating a framework that guarantees the sustainable conservation of marine living resources in Nigeria, particularly fisheries. According to the study, fisheries must be conserved if they are to remain productive for a very long time. It describes the opportunities and difficulties facing the Nigerian fishing regime and suggests ways to achieve long-term preservation of the fishery resources in the Nigerian marine environment.